2023
DOI: 10.1002/em.22525
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative interpretation of ToxTracker dose–response data for potency comparisons and mode‐of‐action determination

Abstract: ToxTracker is an in vitro mammalian stem cell-based reporter assay that detects activation of specific cellular signaling pathways (DNA damage, oxidative stress, and/or protein damage) upon chemical exposure using flow cytometry. Here we used quantitative methods to empirically analyze historical control data, and dose-response data across a wide range of reference chemicals. First, we analyzed historical control data to define a fold-change threshold for identification of a significant positive response. Next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…ToxTracker uses a panel containing six green fluorescent reporter proteins, one for each cell line, to evaluate the ability of genotoxic agents to react with genetic material. The result of this interaction may be blocking of DNA replication, induction of oxidative stress, activation of reactions mediated by denaturation of proteins or general reactions of cellular stress, dependent on the transcription factor R5, which serves as a suppressor of tumor growth [212,213]. The ToxTracker system allows determining the genotoxic potential of the test compound in one test, taking into account various endpoints of DNA damage [213].…”
Section: Modern Methods For Assessing the Genotoxicity Of Environment...mentioning
confidence: 99%
“…ToxTracker uses a panel containing six green fluorescent reporter proteins, one for each cell line, to evaluate the ability of genotoxic agents to react with genetic material. The result of this interaction may be blocking of DNA replication, induction of oxidative stress, activation of reactions mediated by denaturation of proteins or general reactions of cellular stress, dependent on the transcription factor R5, which serves as a suppressor of tumor growth [212,213]. The ToxTracker system allows determining the genotoxic potential of the test compound in one test, taking into account various endpoints of DNA damage [213].…”
Section: Modern Methods For Assessing the Genotoxicity Of Environment...mentioning
confidence: 99%
“…This twofold increase as cut-off for a positive response is based on three times the standard deviation (SD) of fluorescence levels in solvent control cultures. The validity of this approach was recently confirmed using a bootstrapping analysis of more than a 1000 vehicle control treated cultures (Boisvert et al, 2023). Compounds were classified as nongenotoxic in ToxTracker if the induction levels of the genotoxicity reporters (Bscl2 and Rtkn) were less than 1.5-fold.…”
Section: Toxtracker Prediction Modelmentioning
confidence: 98%
“…The criteria for a positive or negative result for each GFP-reporter, were previously established (Boisvert et al, 2023;Hendriks et al, 2016) and are defined in Table 1. GFP reporter inductions at concentrations inducing ≤75% cytotoxicity were acceptable for Tox-Tracker analysis.…”
Section: Toxtracker Prediction Modelmentioning
confidence: 99%
“…The detection of GFP fluorescence in the Bscl2-GFP and Rtkn-GFP cell lines is indicative of DNA replication inhibition and DNA damage, respectively (Hendriks et al, 2016). The ToxTracker assay has been applied to assess over 120 chemicals with different MOAs and quantitative analyses have demonstrated that ToxTracker-informed potency determinations are more informative than simply using the data qualitatively for hazard identification (Boisvert et al, 2023;Wills et al, 2021a). Extended validation studies of the ToxTracker assay are currently being conducted and the information will be used to draft a detailed review paper in support of TG development.…”
Section: Indicator Assaysmentioning
confidence: 99%